Loss of Perivascular Adipose Tissue on Peroxisome Proliferator–Activated Receptor-γ Deletion in Smooth Muscle Cells Impairs Intravascular Thermoregulation and Enhances Atherosclerosis - Chang, Lin; Villacorta, Luis; Li, Rongxia; Hamblin, Milton; Xu, Wei; Dou, Chunyan; Zhang, Jifeng; Wu, Jiarui; Zeng, Rong; Chen, Y. Eugene (Circulation (New York, N.Y.), 2012)
Perivascular adipose tissue (PVAT) surrounds most vessels and shares common features with brown adipose tissue (BAT). Although adaptive thermogenesis in BAT increases energy expenditure and is beneficial for metabolic diseases, little is known about the role of PVAT in vascular diseases such as atherosclerosis. We hypothesize that the thermogenic function of PVAT regulates intravascular temperature and reduces atherosclerosis. PVAT shares similar structural and proteomics with BAT. We demonstrated that PVAT has thermogenic properties similar to BAT in response to cold stimuli in vivo. Proteomics analysis of the PVAT from mice housed in a cold environment identified differential expression in proteins highly related to cellular metabolic processes. In a mouse model deficient in peroxisome proliferator-activated receptor-γ in smooth muscle cells (SMPG KO mice), we uncovered a complete absence of PVAT surrounding the vasculature, likely caused by peroxisome proliferator-activated receptor-γ deletion in the perivascular adipocyte precursor cells as well. Lack of PVAT, which results in loss of its thermogenic activity, impaired vascular homeostasis, which caused temperature loss and endothelial dysfunction. We further showed that cold exposure inhibits atherosclerosis and improves endothelial function in mice with intact PVAT but not in SMPG KO mice as a result of impaired lipid clearance. Proinflammatory cytokine expression in PVAT is not altered on exposure to cold. Finally, prostacyclin released from PVAT contributes to the vascular protection against endothelial dysfunction. PVAT is a vasoactive organ with functional characteristics similar to BAT and is essential for intravascular thermoregulation of cold acclimation. This thermogenic capacity of PVAT plays an important protective role in the pathogenesis of atherosclerosis.